FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA MASERASI STOMA PADA PASIEN YANG TERPASANG KOLOSTOMI DI RSUP DR WAHIDIN SUDIROHUSODO MAKASSAR - Maryunis, Maryunis; Hastuti, Hastuti (in process)
Background: Colorectal cancer is highly prevalent cancer. Colostomy may affect the changing role of self-esteem, body image, and sexual and social relationships. Post-colostomy problem is the maceration of the skin surrounding the stoma. Aim: This study aimed to determine the factors associated with the occurrence of maceration of the stoma in patients who underwenta colostomy in Dr Wahidin Sudirohusodo Hospital of Makassar. Methods: This study used observational analysisby cross-sectional study. The sampling technique was a purposive sampling with 32 âârespondents. Data analysis was done using the Chi Square test with a confidence level of 95%. All data were analyzed by SPSS software,version 21.0 (SPSS, Inc. Chicago, IL). Results: There are relationships between stoma site (p = 0.000), frequency of stoma care (p = 0.018), and nutritional status (p=0.030) with the maceration of the stoma. There was no association betwen age and maceration of the stoma (p = 0.212). Conclusion: This study shows that the factors that affect the skin maceration around the stoma can be modified (frequency of stoma care and nutritional status), while the location factor can be minimized through the stoma sitting. Thus, the nurses have an important role in the prevention of maceration both at pre and post operative Keywords: stoma site, frequency of stoma care, nutritional status, maceration of stoma.